2005
DOI: 10.1089/jmf.2005.8.154
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Radioprotection and Anti-Tumor Immunity by Yeast-Derived β-Glucan in Mice

Abstract: Intraperitoneal injection of beta-glucan was shown to greatly delay mortality in mice exposed to whole-body X-ray radiation and tumor growth in tumor-bearing mice. Since the leukocyte and lymphocyte numbers were increased by a single dose of beta-glucan, the radioprotective effect of beta-glucan is probably mediated, at least in part, by a hemopoietic action in irradiated mice. In addition, both natural killer (NK) and lymphokine-activated killer (LAK) activities were significantly increased by repeated doses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0
5

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 46 publications
(32 citation statements)
references
References 23 publications
1
23
0
5
Order By: Relevance
“…También se han reportado efectos antimutagénicos (46, 47) quimioprotectores y anticancerígenos de estos compuestos (48)(49)(50)(51). Hay pocos estudios realizados en humanos con el β-glucano PGG.…”
unclassified
“…También se han reportado efectos antimutagénicos (46, 47) quimioprotectores y anticancerígenos de estos compuestos (48)(49)(50)(51). Hay pocos estudios realizados en humanos con el β-glucano PGG.…”
unclassified
“…-glucans are acknowledged to be one of the immune response modifiers [6]. Studies conducted over the past decade have shown that -glucans inhibit tumor development [28,38], enhance defense against bacterial infection [15,24], activate macrophages [8], induce production of cytokines [10,34], nitric oxide (NO) and arachidonic acid metabolites [14,21], increase hematopoiesis [35], exert radioprotective effects [12], are effective against burns [9,37], improve wound healing by inducing the macrophage release of wound growth factors [40] and lower serum lipids [4,23]. Among the several mechanisms proposed for the protective effects of -glucans, the major one is related to antioxidant capacity of the molecules [1,20], which has been further proven by Kogan et al [16] using electron paramagnetic response spectroscopy.…”
mentioning
confidence: 99%
“…Some studies indicated that the solubility of these compounds is very important for anti-tumor activity, as more water soluble molecules are more active against cancer cells (Tao et al, 2006;Bohn and BeMiller, 1995). Studies on animal models indicated that several fungal β-glucans may also be helpful during chemotherapy and radiation treatments (Harada et al, 2002;Gu et al, 2005).…”
Section: β-Glucans and Their Physiological Activitiesmentioning
confidence: 99%